Blind gastric biopsy in the diagnosis of Helicobacter Pylori infection - Meral AKDOĞAN; Ali MERT; Süha GÖKSEL; Recep ÖZTÜRK; Sebati ÖZDEMİR and Abdullah SONSUZ and Hakan ŞENTÜRK (Turkish Journal of Gastroenterology, 2019)
-